2021
DOI: 10.1371/journal.pone.0245242
|View full text |Cite
|
Sign up to set email alerts
|

Running prevalence in Portugal: Socio-demographic, behavioral and psychosocial characteristics

Abstract: The purpose of this study was to cross-sectionally estimate the prevalence of recreational running in Portugal and describe characteristics of adult recreational runners. A random representative sample of 1068 Portuguese adults was selected. Socio-demographic information, physical activity habits and running behavior were assessed. Recreational runners’ training habits, motivations, barriers, vitality and flow were also assessed. The prevalence of recreational running in Portugal was 10.6%. It was higher in me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Motives such as competition and health (Ogles and Masters, 2000) or personal goal achievement (Pereira et al, 2021) were associated with weekly training distance, while enjoyment anticipated the adoption of regular running (Titze et al, 2005). Although one study found an interaction between high enjoyment and high family support in the prediction of running behavior (Titze et al, 2005), another found no significant main or interaction effects of social condition (Carnes et al, 2016).…”
Section: Antecedents Of Recreational Runningmentioning
confidence: 99%
See 4 more Smart Citations
“…Motives such as competition and health (Ogles and Masters, 2000) or personal goal achievement (Pereira et al, 2021) were associated with weekly training distance, while enjoyment anticipated the adoption of regular running (Titze et al, 2005). Although one study found an interaction between high enjoyment and high family support in the prediction of running behavior (Titze et al, 2005), another found no significant main or interaction effects of social condition (Carnes et al, 2016).…”
Section: Antecedents Of Recreational Runningmentioning
confidence: 99%
“…Studies comparing motives between different groups found that age (Ogles and Masters, 2000), gender (Tjelta et al, 2017), experience in running (Masters and Ogles, 1995), training profile (Ogles et al, 1995), and type of event (Doppelmayr and Molkenthin, 2004) were associated with different motives. Younger runners were more motivated by personal goal achievement and competition (Pereira et al, 2021). In opposition, older runners were more motivated by health orientation, weight concern, life meaning, and affiliation with other runners (Ogles and Masters, 2000).…”
Section: Antecedents Of Recreational Runningmentioning
confidence: 99%
See 3 more Smart Citations